Lack of interference with diagnostic testing for tuberculosis in goats experimentally exposed to Corynebacterium pseudotuberculosis. Issue 1 (July 2015) - Bezos, Javier; Casal, Carmen; Romero, Beatriz; Liandris, Emmanouil; Sánchez, Natalia; Vigo, Virginia; Domínguez, Lucas; de Juan, Lucía
Highlights: Corynebacterium pseudotuberculosis might cross-react in the tuberculin test. Caprine caseous lymphadenitis does not interfere with diagnostic testing for tuberculosis. The single comparative intradermal tuberculin test is recommended to minimise false positives. Abstract: It has been suggested that infection with Corynebacterium pseudotuberculosis, the pathogen responsible for caseous lymphadenitis (CLA), might interfere with diagnostic testing for tuberculosis (TB), due to antigenic similarities between this particular type of bacterium and those expressed by mycobacteria. The aim of the present study was to investigate whether experimental infection with C.   pseudotuberculosis in goats impacted on TB testing, using single and comparative intradermal tuberculin (SIT and SCIT respectively) tests and interferon (IFN)-γ assay. No positive reactors were detected among the CLA-affected goats using the SIT/SCIT tests or the interferon IFN-γ assay. A proportion of goats showed inconclusive results to the SIT test and reactions to Mycobacterium avium . There was no evidence that infection with C.   pseudotuberculosis interferes with diagnostic testing for TB using standard interpretation of the SIT, SCIT and IFN-γ tests.